The relationship between personality, emotional intelligence, sociodemographic factors and work-family spillover - Nurhamiza Mumin @ Osman (2017)
Individuals respond differ-ently when occupying multiple social roles. Some tend to report positive experiences, whereas others fail to balance work and family responsibilities. This study examined the effects of personality, emotional intelligence (EI) and socio-demographic background on work-family spillover. Service industry employees in five major cities were recruited via e-mail and social media. Questionnaires were distributed to banks, schools, and private and public health care providers. Service companies in Kata Kinabalu, Kuala Lumpur, Shah Alam, Klang and Kuching were included in this survey and data from 531 respondents was collected. Personality and EI effects were analysed using SmartPLS. Regression-based analysis was used to examine the role of sociodemographic background on work-family spillover. Personality was found to be a significant factor in the work-family conflict, but only neuroticism had significant effects on family-to-work enrichment (FWE). Managing one's own emotions, managing others' emotions, and utilizing emotions were shown to be key EI abilities that determine work-family spillover. Socio-demographic factors, such as age, gender, ethnicity, and length of service strongly influenced the family-to-work conflict (FWC). Ethnicity and the level of education further contributed to workfamily enrichment. Moreover, ethnicity was shown to play a significant role in the work-to-family conflict (WFC). The findings of this study indicate that ethnicity contributes to different magnitude of work-family experience in multicultural countries, such as Malaysia. Overall, the present work provided empirical data to describe how personality and EI contributed to a positive or a negative work-family spillover experience. It offered a better understanding of the interactions between selected personal and professional characteristics, and work-family conflict and work-family enrichment. The present findings may serve to develop better work arrangements and policies to allow workers to accommodate their multiple social responsibilities.